Multimedia geocoding: The RECOD 2014 approach - Li, Lin Tzy; Penatti, Otávio A. B.; Almeida, Jurandy; Chiachia, Giovani; Calumby, Rodrigo T.; Júnior, Pedro R. Mendes; Pedronette, Daniel C. G. [UNESP]; Torres Da, Ricardo S. (My University, 2014)
This work describes the approach proposed by the RECOD team for the Placing Task of MediaEval 2014. This task requires the definition of automatic schemes to assign geographical locations to images and videos. Our approach is based on the use of as much evidences as possible (textual, visual, and/or audio descriptors) to geocode a given image/video. We estimate the location of test items by clustering the geographic coordinates of top-ranked items in one or more ranked lists defined in terms of different criteria.
Keywords: Descriptors; Geo coding; Geographic coordinates; Geographical locations